Improving Drought Tolerance in Chili Pepper by the Application of Local Microorganisms (LMo) - Eliyanti Eliyanti; Zulkarnain Zulkarnain; Budiyati Ichwan; Trias Novita; Janes Sihotang (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
his study aimed at determining the effect of spraying intervals of local microorganism (MoL) golden apple snails on the improvement of drought tolerance of chili grown under limited water availability. The trial was carried out at greenhouse and Plant Protection Laboratory, Faculty of Agriculture, University of Jambi for 6 months. The study used a Randomized Block Design with 2 factors and 3 replications. The first factor was the chili cultivar consisted of Vitra, Lado and Laris. While the second factor was the spraying interval of MoL golden apple snail consisted of 100% field capacity of soil water without MoL application, 75% field capacity of soil water and spraying intervals once a week, and 75% field capacity of soil water and spraying intervals every two weeks. The results showed that spraying MoL golden apple snail at intervals of either once in 1 or 2 weeks could increase tolerance to drought stress in three chili cutivars grown under 75% field capacity of soil water. Plant growth and yield at 75% field capacity of soil water was the same as that of plants grown under optimum conditions (100 % field capacity of soil water), MoL spray on the cv. Vitra could increase fruit weight per plant by up to 32% over fruit weight of those plants grown under optimum conditions.